Republic of Uzbekistan : Requests for Disbursement under the Rapid Credit Facility and Purchase under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Uzbekistan. (IMF Staff Country Reports; Country Report, 2020)
This paper examines Republic of Uzbekistan's Requests for Disbursement Under the Rapid Credit Facility (RCF) and Purchase Under the Rapid Financing Instrument (RFI). The coronavirus disease 2019 pandemic is significantly impacting Uzbekistan's economy, reducing growth, and creating additional external and fiscal financing needs. IMF financial assistance under the RCF and the RFI, along with support from other multilateral institutions, will help cover Uzbekistan's fiscal and balance of payments needs and mitigate the impact on its foreign exchange reserves. It will also provide resources to support increased crisis spending for healthcare, social protection, and public support for affected firms and households. Uzbekistan aims to continue implementing its structural reform agenda, to complete the transformation to a modern, open market economy, and to improve governance and public management. It has committed to safeguard the use and improve the efficiency of its public resources by increasing transparency and accountability.